Experimental Venous Thrombosis in Alloxan Diabetic Rats - Nordöy, Arne (Thrombosis and Haemostasis, 1964)
1. The effect of alloxan diabetes on thrombus formation has been examined in rats using a standardized damage of the jugular vein. No significant increase in the incidence of thrombosis as compared with the control group was observed.2. An accelerated recalcification time, cephalin time and thromboplastin time was observed, as well as an increase in the levels of fibrinogen, factor VII and factor VIII.3. The ADP-induced platelet adhesiveness in platelet rich plasma was decreased, possibly indicating a decrease in anti-Willebrand factor.4. A slight increase in total cholesterol, free fatty acids and triglycerides in plasma was observed.5. It is concluded from the present study that a thrombotic condition is not present in alloxan diabetic rats, although the activity of some coagulation factors is increased. The reason for this may be the decreased ADP-induced platelet adhesiveness in plasma.